Degrees of change: the promise of anti-racist assessment - Green, Melissa; Malcolm, Claire (Frontiers in Sociology, 2023)
Assessment practices in Higher Education remain beholden to the twin pillars of neoliberal economic orthodoxy and white supremacy. The former has given rise to the modularization and commodification of education, wherein student performance is measured according to narrow and often meaningless metrics that foster and maintain ineffective assessment mechanisms. The latter imbues those metrics with a deference to, and valorization of, "Whiteness" as a marker of success, and this manifests in persistent awarding gaps across the sector. Critical Race Theory elucidates the ways in which the "banking model" of education and assessment is implicated in a history of colonial oppression that underpins contemporary experiences of marginalization for racially minoritised students. Furthermore, the rapid proliferation of Artificial Intelligence programs is now throwing into sharp relief the fact that traditional forms of assessment are no longer functional even on their own flawed terms. The authors argue that, at this critical juncture, Anti-Racist assessment, which not only exposes and problematizes racism itself but also embeds formative feedback, drafting, collaboration, and creativity into assessment practices, offers a practical solution that can reconceptualize 'academic excellence' and help to identify and support a different kind of 'good student', reshaping the employability agenda as a force for good and reclaiming the democratizing potential of Higher Education.